Fifteen Minutes of Fame The Place Prize reviewed - Roy, Sanjoy (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Review of The Place Prize. PALABRAS CLAVE: The Place Prize, contemporary dance award, Rafael Bonachella, E2 7SD.